2017
DOI: 10.1051/0004-6361/201630165
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy kinematics in the XMMU J2235-2557 cluster field at z ~ 1.4

Abstract: Aims. The relationship between baryonic and dark components in galaxies varies with the environment and cosmic time. Galaxy scaling relations describe strong trends between important physical properties. A very important quantitative tool in case of spiral galaxies is the Tully-Fisher relation (TFR), which combines the luminosity of the stellar population with the characteristic rotational velocity (V max ) taken as proxy for the total mass. In order to constrain galaxy evolution in clusters, we need measureme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 72 publications
(115 reference statements)
1
19
0
Order By: Relevance
“…We have, moreover, repeated the same analysis by using the normalized scatter around the relation for only the rotation dominated galaxies, and we found that the conclusion is invariant. This result is consistent with past studies (e.g., Bösch et al 2013;Pérez-Martínez et al 2017) that have found no evidence of environmental effect on the smTFR.…”
Section: Stellar Mass Tully-fisher Relationsupporting
confidence: 93%
See 1 more Smart Citation
“…We have, moreover, repeated the same analysis by using the normalized scatter around the relation for only the rotation dominated galaxies, and we found that the conclusion is invariant. This result is consistent with past studies (e.g., Bösch et al 2013;Pérez-Martínez et al 2017) that have found no evidence of environmental effect on the smTFR.…”
Section: Stellar Mass Tully-fisher Relationsupporting
confidence: 93%
“…A few works have studied the dependence of the TFR and smTFR on the environment. At z ≥ 0.1 some authors investigated the effects of the environment, defined as "cluster" or "field" (Bösch et al 2013;Pérez-Martínez et al 2017) or by local density (Pelliccia et al 2017), on the smTFR and found no variations in the relation. This may be a consequence of small sample of galaxies, especially in the higher density regions (i.e., cluster core or highest local overdensity).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the new large samples presented above, studying the impact of environment on the TFR is not yet possible at intermediate redshift since very little is known about the density field in which those galaxies reside, due to incomplete spectroscopic coverage. Some studies have, however, targeted a few dozen galaxies in groups and (proto-)clusters at intermediate redshift with KMOS and FORS2 (e.g., Sobral et al 2013;Pérez-Martínez et al 2017;Böhm et al 2020). So far, the most complete study of the TFR as a function of environment has been performed from long-slit spectroscopy observations by Pelliccia et al (2019), using a sample of 94 galaxies at z ∼ 1, a fraction of which were members of clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Current work has extended these observations to much higher redshifts, with studies of protoclusters and overdensities at redshifts between 1.5 < z < 2.5 becoming common (e.g. Muzzin et al 2013;Shimakawa et al 2015;Wang et al 2016b;Prichard et al 2017;Pérez-Martínez et al 2017;Böhm et al 2020; see Overzier 2016 for a review).…”
Section: Introductionmentioning
confidence: 99%